Influencing Factors in Patient Referrals: A Doctor’s Perspective on Primary Health Care Facilities (FKTP) - Ridwan, Ridwan; Ramadhan, Syahru (BPJS Kesehatan, 2025)
An effective and efficient referral system is essential for ensuring patients receive the appropriate treatment for their medical conditions. Primary Health Care Facilities (FKTP) play a critical role in addressing the healthcare needs of patients at the first level. Despite receiving 100% Performance-Based Capitation (KBK), FKTPs exhibit a high referral rate, as indicated by referral rates, referral ratios, and Non-Specialist Referral (RNS) metrics. This quantitative study explores the factors influencing patient referrals in FKTPs, as perceived by doctors. A structured questionnaire was used to gather data from 69 doctors across 148 FKTPs in the BPJS Kesehatan Branch of Banda Aceh in July 2024. The survey addressed various aspects, including doctors' competence, patient behavior, FKTP capabilities, and referral mechanisms. The results revealed that the location of health facilities significantly impacts referral rates and healthcare costs, with facilities located closer to villages reducing the need for referrals and enhancing healthcare accessibility for remote populations. BPJS Kesehatan can improve collaboration with FKTPs by identifying strategic locations in rural areas and leveraging the Aplicares web to map and optimize health services. Furthermore, the government could enhance healthcare access by creating maps to develop public health centers in rural areas or collaborating with private and family doctors to expand services in underserved regions. This study provides valuable insights for policymakers, suggesting that improving FKTP accessibility and addressing resource limitations could significantly reduce unnecessary referrals, lower healthcare costs, and improve the efficiency of the healthcare system in rural areas.